Uso de nutracêuticos na terapêutica da anorexia associada ao câncer: revisão sistemática de estudos em humanos e em modelos experimentais - Wesley Cardoso Silva (2022)
Cancer-related anorexia (ARC) is a complex pathological condition in which the involuntary loss of appetite in individuals with cancer occurs due to systemic metabolic and immunological abnormalities triggered by tumor chemical mediators. ARC is a very frequent symptom of the paraneoplastic syndrome known as cancer-associated cachexia (CAC). The aim of this study was to update information on the use of nutraceutical agents in the clinical management of ARC from a systematic review of human clinical studies and in a murine tumor model. A systematic literature search was performed using keywords in multiple electronic databases from 1999 to 2021. Studies that used dietary nutraceuticals for the clinical management of ARC in human populations and in a murine tumor model were included. In animal studies, changes in body weight and appetite during the treatment period were evaluated to define CAC and ARC, respectively. The PRISMA protocol was used for selection of human and murine tumor model studies. Human studies with a randomized clinical trial design were considered, as well as simple reviews. The methodological quality of the studies was performed using the Jadad Scale. A systematic literature search resulted in the identification of 43 publications, 10 of which met the inclusion criteria, 6 for animal studies and 4 for human studies. The use of nutraceuticals to stimulate appetite and body weight gain was more commonly observed in a mouse and mouse xenotransplantation tumor model, via subcutaneous inoculation of immortalized human cancer cells of different strains. There are many variations in terms of sex and murine species and the type of cancer cell used in ARC studies with a tumor model. The nutraceuticals that promoted a significant increase inappetite in the animals were a diet with 4.6% L-leucine, a diet containing 5% pectic oligosaccharides and a standard diet containing 1% Rikkunshito. In human studies, the diagnosis of ARC was defined using subscales of the Analogic visual scale (VAS), European Organization for Cancer Research and Treatment Quality of Life Questionnaires (EORTC- QLQ-C30), Center-North Cancer Treatment Group (NCCTG and FAACT). Most of thesubjects in the studies were male. The types of cancer most frequently investigated in the studies were lung cancer, followed by gastrointestinal cancer and the nutraceuticals that showed antianoretic effects were cannabinoids and polyphenols. These nutraceuticals promoted an improvement of appetite and body weight in individuals with different types of cancer. The risk of bias in individual studies was assessed according to methodological quality using the Jadad scale. The cut-off points were: level A = 4 points; level B = 3-2 points; level C ≤ 2 points. Studies with a score of less than three points were considered as having a low quality referred scale. Thus, there is therapeutic potential of certain nutraceuticals for the management of ARC. Future investigations are essential to identify natural foods that can improve the quality of life of individuals with cancer.